Rainwater Percolation Dynamics Assessment through the Vadose Karst Zone on the Basis of Discharge Measurements - Kogovšek, Janja (Acta Carsologica, 2007)
Researches based on seasonal and later continuous measurements of precipitation on the surface and discharges of typical trickles in Postojnska Jama, 100 m below the surface, showed the dynamics of percolation in a period of a hydrological year. They registered summer periods lasting several months when all the rainfall, even more abundant, is stored in a vadose zone. After a longer dry period the first discharge reactions of trickles to rainfall strongly differ while there is no substantial difference in a wet period. The water outflow in decreasing parts of water pulses essentially differs among various trickles and we recognised the types of trickles feeding karst aquifers even during low water level or low discahrges of karst springs.